Uma análise das políticas públicas de inclusão digital na Região Metropolitana da Grande Vitória/ES - Mantovani, Ailton (2017)
This dissertation aims to establish an analysis of the public policies of digital inclusion implemented in the municipalities that compound theMetropolitan Region of Greater Vitória/ES, based on contextual and objective elements and under the view of the mechanisms of social inclusion. In order to set theparameters for this analysis, we sought to highlight the context of the conceptual formation of the term digital exclusion and the approaches to its treatment, especially those globally recognized, as well as those adopted by the Brazilian federal government. In this search, similarities and distinctions between social exclusion and digital exclusion were highlighted and a historical review of the development of public policies of digital inclusion in Brazil was done. It was established the idea that digital inclusion should be understood as "providing access", "digital literacy" and "appropriation of technologies" aiming the social inclusion. In addition, the principles from which the brazilian federal government decided to implement its public policies were revealed. The study goes into identifying the digital inclusion initiatives implemented by the municipalities in their territory and the problems faced in this process. It was verified that the public policies of digital inclusion in the studied municipalities suffer the same problems of the brazilian social policies: the fragmentation, the administrative discontinuity and the high dependence of the resources of federal origin. The municipalities presented a great disparity in the number and scope of the inclusive measures, aggravated by the evident unfamiliarity of the concept and utility of digital inclusion by the public managers. Finally, it was identified a lack of available indicators to measure digital exclusion and inclusion revealing the need of developing indicators to assess the social inclusion achieved through the implementation ofdigital inclusion actions.